Korean Red Ginseng Extract Enhances the Anticancer Effects of Imatinib Mesylate Through Abrogation p38 and STAT5 Activation in KBM‐5 Cells. (8th April 2015) - Jung, Sang Yoon; Kim, Chulwon; Kim, Wan‐Seok; Lee, Seok‐Geun; Lee, Jun‐Hee; Shim, Bum Sang; Kim, Sung‐Hoon; Ahn, Kyoo Seok; Ahn, Kwang Seok
<x xml:space="preserve">Abstract</x> Although imatinib mesylate (IM) in the treatment of chronic myelogenous leukemia (CML) remains the best example of successful targeted therapy, majority of patients with CML suffer its toxicity profile and develop chemoresistance to existing therapeutic agents. Thus, there is a need to develop novel alternative therapies for the treatment of CML. Here, we investigated whether Korean red ginseng extract (KRGE) could suppress the proliferation and induce chemosensitization in human CML cells. Also, we used a human phospho‐antibody array containing 46 antibodies against signaling molecules to examine a subset of phosphorylation events after treatment. Korean red ginseng extract broadly suppressed the proliferation of five different cell lines, but KRGE was found to be the most potent inducer of apoptosis against KBM‐5 cells. It also abrogated the expression of Bcl‐2 (B‐cell lymphoma 2), Bcl‐xL (B‐cell lymphoma‐extra large), survivin, inhibitors of apoptosis protein 1/2, COX‐2 (Cyclooxygenase‐2), cyclin D1, matrix metalloproteinase‐9, and VEGF (Vascular endothelial growth factor), as well as upregulated the expression of pro‐apoptotic gene products. Interestingly, KRGE also enhanced the cytotoxic and apoptotic effect of IM in KBM‐5 cells. The combination treatment of KRGE and IM caused pronounced suppression of p38 and signal transducer and activator of transcription 5 phosphorylation and induced phosphorylation of p53 compared with the individual treatment. Our results demonstrate that KRGE can enhance the anticancer activity of IM and may have a substantial potential in the treatment of CML. Copyright © 2015 John Wiley & Sons, Ltd.